Review of the Doctrine of Dilution Based on the Perspective of Corrective Justice for Trademark Owners - Sukma Hidayatun Nahdliyin; Emmy Latifah (Fakultas Hukum Universitas Muhammadiyah Sorong, 2026)
The study aims to analyze whether the doctrine of trademark dilution has provided corrective justice or otherwise, so that the balance of rights for trademark owners can be fulfilled.The methods used in this study are normative or doctrinal legal research methods. The research approaches used are legislative, conceptual, case-based, and comparative approaches.The novelty of this research lies in the perspective of corrective justice in analyzing court decisions related to dilution actions. This research is expected to contribute to further research and policy recommendations for the government and judges to produce regulations and decisions that are fair to trademark owners.The results of the comparative law study show that anti-dilution regulations in the United States are comprehensively regulated, but there are shortcomings in the courts. Court decisions regarding well-known trademarks are considered detrimental and do not restore the rights that have been violated. In fact, the main purpose of dilution is to provide legal protection for well-known trademarks. Indonesia itself has not yet fully regulated anti-dilution regulations.The concluded findings of this comparative legal study serve as a lesson for Indonesia so that future regulations can take into account the balance of rights between well-known trademarks and other trademarks in order to avoid market monopoly.